2001
DOI: 10.1103/physrevlett.86.3344
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Correlations and the Structure of Nonequilibrium Hard-Core Fluids

Abstract: A model for the pair distribution function of nonequilibrium hard-core fluids is proposed based on a model for the effect of velocity correlations on the structure. Good agreement is found with molecular dynamics simulations of granular fluids and of sheared elastic hard spheres. It is argued that the incorporation of velocity correlations are crucial to correctly modeling atomic scale structure in nonequilibrium fluids.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…These include phenomenological approaches based on fluctuating hydrodynamics [1][2][3] and on the Langevin models [4,5]. More recently a relatively successful description of the structural changes in the hardsphere fluid under shear was given by Lutsko [6], where he combines solution of the Enskog equation [7], which gives the contact value of the hard-sphere pair distribution function, and ideas of the generalized mean spherical approximation approach [8].…”
Section: Introductionmentioning
confidence: 99%
“…These include phenomenological approaches based on fluctuating hydrodynamics [1][2][3] and on the Langevin models [4,5]. More recently a relatively successful description of the structural changes in the hardsphere fluid under shear was given by Lutsko [6], where he combines solution of the Enskog equation [7], which gives the contact value of the hard-sphere pair distribution function, and ideas of the generalized mean spherical approximation approach [8].…”
Section: Introductionmentioning
confidence: 99%
“…The paper ends with a discussion of the prospects to extend these results to other systems. A preliminary description of some of these results has appeared previously [3].…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are constrained by two boundary conditions consisting of the values of M 00 and M 22 . In the first application to shear flow [3], the model was simplified by setting K 00 = K 22 = 0. The justification for this was simplicity, since there is then only the non-uniqueness parameter, B 22,1 , and it was shown that a value could be found which simultaneously satisfied both boundary conditions reasonably well.…”
Section: B Langevin Model For Density Fluctuationsmentioning
confidence: 99%
See 2 more Smart Citations